A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMP NEGERI 1 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Afrita Herneti; Supriusman Supriusman; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was aimed at finding out the reading ability of the first year students of SMP Negeri 1 Pekanbaru in comprehending descriptive texts. The population of this research was the first year students of SMP Negeri 1 Pekanbaru. The number of sample was 34 students selected by using cluster random sampling technique. The instrument to collect the data was multiple choice test items with 30 questions. Each text consists of 6 questions which cover the components of reading and the components of descriptive namely finding main ideas, finding factual information, finding meaning of vocabulary words, finding references, finding inferences and finding social functions. The data were analyzed by classifying them into five levels of ability: very poor, poor, mediocre, good and excellent. Based on the findings of this research, it was found that the students’ reading ability of the first year students of SMP Negeri 1 Pekanbaru in comprehending descriptive texts was in good level with the mean score was 61. The implication of this research is that the first year students of SMP Negeri 1 Pekanbaru have a good ability in reading descriptive texts.Key Words: Students’ ability, Reading, Descriptive Texts.